Does Violent Conflict Affect Labor Supply of Farm Households? The Nigerian Experience - John Chiwuzulum Odozi; Ruth Uwaifo Oyelere (Institute of Labor Economics (IZA), 2021)
Nigeria has experienced bouts of violent conflict in different regions since its independence leading to significant loss of life. In this paper, we explore the average effect of exposure to violent conflict generally on labor supply in agriculture. Using a nationally representative panel dataset for Nigeria from 2010-2015, in combination with armed conflict data, we estimate the average effect of exposure to violent conflict on a household's farm labor supply. Our findings suggest that on average, exposure to violent conflict significantly reduces total family labor supply hours in agriculture. We also find that the decline in family labor supply is driven by a significant decline in the household head's total number of hours on the farm.
Keywords: Q10; Q12; O1; D74; 330; ethno-religious conflict; Boko Haram; farm households; farmer-herdsmen conflict; labor supply; Nigeria; Niger-delta conflict; violent conflict